Preliminary profile of ICT-Based SMEs in adopting knowledge management - Minah Japang; Caroline Jeffrey; Rostinah Supinah; Ainnecia Yoag (2016)
The focal point of this paper is to: (a) present the pilot profiles of ICT-based SMEs operating in Sabah and Labuan; (b) identify the descriptive component of the technology or business focus of these ICT-based SMEs; and (c) to contribute type of important knowledge stream that is perceived to be significance for ICT-based SMEs’ competitiveness. This preliminary study ofICT-based SMEs tried to provides a comprehensive definition of ICT-based SMEs types and size based on the number of full time employees. The findings indicates that out of overall SMEs in services, primary agriculture and ICT sectors, there are approximately 36% (23) ICT-based SMEs which are micro-enterprises, 37% (24) are small-enterprises and 27% (17) are medium-enterprises. In terms of critical important knowledge stream that is perceived to be significant for ICT SMEs’ competitiveness, results show that almost all nine knowledge stream are perceived to be important. However, knowledge about own products and services are perceived to be the most important with mean value of 4.47 (standard deviation: 0.71). The second component perceived as important is retaining customer loyalty through keeping tracks with knowledge about customers with mean value of 4.25 (0.78) as well as knowledge about latest technology (mean = 4.13, standard deviation = 0.86) as compared to 4.08 and 4.02 mean values for knowledge about their own competencies or capabilities and finding out the best vendor or supply chain, respectively.